Taxonomic account of jumping spiders – Genus Marpissa C. L. Koch (Archnida: Araneae: Salticidae) from Bangladesh - Biswas, V; Raychaudhuri, D (Journal of Biodiversity Conservation and Bioresource Management, 2022)
A taxonomic study on the jumping spiders’ genus Marpissa C.L. Koch, 1846 was carried out from different areas of Bangladesh. Four species were identified from the study, namely M. andamanensis Tikader, M. bengalensis Tikader, M. calcuttaensis Tikader and M. decorata Tikader. All the species are illustrated and described in detail for the first time in Bangladesh. Generic diagnosis, distribution and key to the species are also provided herewith J. Biodivers. Conserv. Bioresour. Manag. 2021, 7(1): 1-10